Pharmacist knowledge and management of LASA medicines in preventing medication error in Semarang Regency Pharmacies - Rahmaniar, Ranita; Dewantara, Aditya Arya; Mubarok, Nala Khodlil; Islami, Bella Citra; Maharani, Eka Putri; Kamilah, Nada Amatullahi (Riset Informasi Kesehatan, 2025)
Background: The development of the pharmaceutical industry has produced drugs with similar names and physical forms, known as LASA. The similarity of LASA drugs is a serious concern because it can cause confusion among pharmacist and increases the possibility of errors at dispensing, such as taking the wrong drug. LASA drug management is pharmacist’s responsibilities in pharmaceutical services. This study aims to evaluate the knowledge of pharmacist and the management of LASA drugs in Semarang Regency Pharmacies. Method: This study is a non-experimental study. Questionnaires were given to pharmacists in Semarang Regency Pharmacies. The results were tested using Chi Square to determine the relationship between knowledge and management, knowledge and errors in taking LASA drugs and management and errors in taking LASA drugs. Results: The results of the study showed that the knowledge of pharmacists >70% was in the good category. LASA drug management has been carried out in >70% of pharmacies. There are still 32.47% medication errors in taking LASA drugs. Analysis showed that there was no significant relationship between knowledge, LASA drug management, and errors in taking LASA drugs. Conclusion: From this study it can be concluded that LASA drug management in Semarang Regency Pharmacies is in the good category.